The DRO procedure and the apparent possibility of using non-aversive procedures in reducing “problem” behaviors (Brazilian Journal of Behavioral and Cognitive Therapy, 2018)
Apparently, there is a consensus on the use of differential reinforcement of other behaviors (DRO) to treat challenging behaviors among children with Autism. This consensus results from an evaluation of DRO as a nonaversive procedure. However, a detailed analysis of the literature of the area do not show this. Therefore, the aim of this paper is to discuss and raise significant questions to produce knowledge and, consequently, possible parameters of intervention using the DRO procedure. It is concluded that the delimitation of the DRO as a nonaversive procedure deserves to be re-evaluated.
Keywords: DRO, aversive control, negative punishment, autism